SKILLS FOR ENGLISH TEACHERS IN MILITARY SCHOOLS - Khalilova , N. (EurasianUnionScientists, 2021)
In the paper it was mentioned efficient skills of teachers for conducting their jobs more effectively. There are a number of skills that apply to each, regardless of which subject the teachers teach. These include preparing lesson plans, choosing the right textbooks and topics, checking assignments in timely manner, doing survey during classes and out of classes, evaluating student’s knowledge. Proper implementation of these skills is very important for every teacher. At the same time, foreign language teachers must have other skills. If the teacher is not a native speaker, he should improve his speech and vocabulary. This is the main duty for foreign language teachers. In addition, they should be able to distinguish between cultures and their impact on speech. Modern technologies, especially computers, must be used properly and applied in teaching.